Kegiatan “Rumah Belajar” Sebagai Media Menganalisis Perilaku Keluarga dengan Risiko Kejadian Balita Stunting - NLP Yunianti Suntari C; I Ketut Gama (Politeknik Kesehatan Tanjung Karang, 2020)
The rate of stunting or dwarf or acute malnutrition in children aged 1000 days in Indonesia is stagnant, which is around 37% of births from 2007 to 2013 (World Bank Report: Aiming High and Riskesdas, 2013). Children who are stunted will be more susceptible to illness and experience a decline in cognitive abilities that impact on the child's economic abilities in the future. Family development and empowerment is part of sensitive nutrition interventions. In carrying out its function role, the family has views and beliefs which will certainly affect the way the family takes care of children. This family paradigm is a basic belief held by the family, and guides actions in caring for and caring for their children. The